2022
DOI: 10.37496/rbz5120220005
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of chia (Salvia hispanica) seeds and oil in broiler diets

Abstract: Non-ruminantsFull-length research article Nutritional evaluation of chia (Salvia hispanica) seeds and oil in broiler diets ABSTRACT -Two experiments were carried with broilers from 29 to 42 days of age for the nutritional evaluation of dietary chia. Thus, the nitrogen-corrected apparent metabolizable energy (AMEn) and the apparent metabolizability coefficients of gross energy and ether extract of chia seeds and oil, toasted soybean grain (TSG), and soybean oil were determined in the experiment I, by total excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These results are in line with those observed by Rasul et al, (2019) who found that, carcass traits including the relative weights of dressing percentage, gizzard, and carcass were significantly improved by using 0.7% chia seeds in the diet of quail. Additionally, Mendonça et al (2022) found that supplementation of 0.025 g chia oil/kg diet or 0.164 g chia seed/kg diet was able to improve significantly the relative weight of carcass (p<0.05).…”
Section: Discussionmentioning
confidence: 97%
“…These results are in line with those observed by Rasul et al, (2019) who found that, carcass traits including the relative weights of dressing percentage, gizzard, and carcass were significantly improved by using 0.7% chia seeds in the diet of quail. Additionally, Mendonça et al (2022) found that supplementation of 0.025 g chia oil/kg diet or 0.164 g chia seed/kg diet was able to improve significantly the relative weight of carcass (p<0.05).…”
Section: Discussionmentioning
confidence: 97%